2004
DOI: 10.1007/s11104-005-2569-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the concentration of phenolic compounds and exudation induced by phosphate deficiency in bean plants (Phaseolus vulgaris L.)

Abstract: The effect of prolonged phosphate starvation of bean plants (Phaseolus vulgaris L.) on the concentration of phenolics and their exudation by roots was studied. Plants cultured on phosphate-deficient media maintained a steady concentration of total phenolics in the leaves, whereas in the leaves of plants grown on complete nutrient media the phenolic concentration decreased. After 18 days of culture, higher total phenolics and anthocyanin concentrations in phosphate-deficient leaves compared with control leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 37 publications
5
54
0
1
Order By: Relevance
“…This is confirmed in the research with bean plants by Jaszczuk et al (2004). In the bean plant with the deficit of phosphorus, the intensity of photorespiration increases, as does the level of glycolic acid.…”
Section: Abiotic Factors -Climate Soil and Agrotechnical Conditionssupporting
confidence: 64%
“…This is confirmed in the research with bean plants by Jaszczuk et al (2004). In the bean plant with the deficit of phosphorus, the intensity of photorespiration increases, as does the level of glycolic acid.…”
Section: Abiotic Factors -Climate Soil and Agrotechnical Conditionssupporting
confidence: 64%
“…Anthocyanin is a secondary metabolite that can be produced in response to oxidative stress, performing important protection roles (Juszczuk et al 2004). Anthocyanin accumulation is a common response of various plant species subjected to different stresses (Valko et al 2006), and its increase in L. gibba after As exposure can aid in oxidative stress protection (Rice-Evans et al 1997).…”
Section: Journal Of Plant Interactions 147mentioning
confidence: 99%
“…These results are in line with results of Gerschenzon (1983) who found that soil defi ciencies in phosphorus, sulphur, iron, calcium, and magnesium stimulates the production of phenolic compounds in plant tissues. Higher phenolic contents have also been reported as a response to phosphate starvation in Phaseolus vulgaris L. (Juszczuk et al 2004). According to Tavarini et al (2015) nitrogen fertilization of soil in the amount of 150 kg per ha will optimize the content of total phenols and fl avonoids in leaves of Stevia rebaudiana Bertoloni (Asteraceae).…”
Section: Correlation Between Phenolic Substances and Chemical Propertmentioning
confidence: 87%